PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA PEGAWAI UPT. TIK UNIVERSITAS TADULAKO - Isnain, Mohamad Nugrah (Katalogis, 2017)
The purpose of this research is to find out and analyze the influence of Intellectual quotient, emotional quotient, and Spiritual quotient on performance Clerk UPT. TIK Untad. The population in this study amounted to 35 people, as it is then not held the withdrawal of samples. Data processing using IBM SPSS Statistics 24 programme, performed statistical tests using multiple linear regression analysis.Â Results of the study showed, (1) Intelligence, emotional Quotient, Intellectual and Spiritual Quotient significant effect simultan eously on performance clerk UPT. TIK Untad, (2) partially influential Intellectual Quotient does not significantly to the performance of the employees of the UPT. TIK Untad, (3) emotional Quotient in partial effect performance significantly to officers of the UPT. TIK Untad,(4) Spiritual Quotient in partial effect significantly to the performance of the employees of the UPT.TIK Untad.